53 Consumer understanding of terms used in imaging reports requested for low back pain. (4th December 2019) - Farmer, Caitlin; O'Connor, Denise; Lee, Hopin; McCaffery, Kirsten; Maher, Christopher; Newell, David; Cashin, Aidan; Byfield, David; Jarvik, Jeffrey; Buchbinder, Rachelle
Abstract : Background: Clinical practice guidelines worldwide consistently recommend against routine lumbar spine imaging for patients with low back pain. Despite this, around 1 in 4 people with low back pain receive imaging, and this is associated with further unnecessary testing and treatment. In the absence of features suggestive of a serious or specific condition imaging is unlikely to provide information to guide treatment yet is likely to reveal age-related changes that are common in asymptomatic people. Language used to describe these imaging findings may lead to clinician concern and patient anxiety, impacting the perceived seriousness and persistence of symptoms and increasing preference for further interventions. Objectives: To investigate the self-reported understanding of commonly used terms in lumbar spine imaging reports in a random sample of the general population, and the relationship between understanding of these terms and worry about perceived seriousness and persistence of the condition. Methods: We conducted an online anonymous cross-sectional survey in April 2019. English-speaking adults from the United States, Canada, United Kingdom, New Zealand and Australia were invited to participate via a survey sampling company (Dynata) using an online survey platform (Qualtrics). Quotas were established for age, gender and country to ensure a representative sample. The survey comprised demographic questions, low back pain history and the Back Beliefs Questionnaire (BBQ) which elicits beliefs about the inevitable consequences of future life with low back problems. We included 14 terms commonly found in lumbar spine imaging reports and common in asymptomatic populations. For each term we elicited self-reported comprehension of the term, its perceived seriousness and whether it indicated likely persistence of pain. We also asked participants whether or not patients should have access to their imaging reports and whether the report should be written in terms understandable to the patient and include information about frequency of abnormalities found in asymptomatic people. A sample size of a minimum of 590 responses was required to ensure sufficient power for a multivariable analysis to explore responses relationship between understanding of terms and worry about perceived seriousness and persistence of the condition. Results: Of 774 responses we excluded 35 that were incomplete (5%), 59 (8%) due to likely invalid answers to the BBQ and 3 (0.4%) who did not fit the inclusion criteria for age. For the remaining 677 responses, there were 354 (52%) females, median (range) age 45 (18 to 84) years and 85% had a current or past history of low back pain. The majority of respondents wanted patients to have access to their imaging reports (N=605, 89%), 586 (87%) wanted reports written in understandable language for the lay public and 587 (87%) wanted information about common findings that occur in asymptomatic people. The full results are currently being analysed and will be available for Preventing Overdiagnosis 2019. Conclusion: Improving the quality and comprehensibility of information provided in the lumbar spine imaging report may lead to better evidence-informed decisions about care for people with low back pain and reduce unwarranted overdiagnosis and overtreatment.